Omics and biotechnology of arsenic stress and detoxification in plants: Current updates and prospective. (January 2015) - Kumar, Smita; Dubey, Rama Shanker; Tripathi, Rudra Deo; Chakrabarty, Debasis; Trivedi, Prabodh Kumar
Abstract: Arsenic (As), a naturally occurring metallic element, is a dreadful health hazard to millions of people across the globe. Arsenic is present in low amount in the environment and originates from anthropogenic impact and geogenic sources. The presence of As in groundwater used for irrigation is a worldwide problem as it affects crop productivity, accumulates to different tissues and contaminates food chain. The consumption of As contaminated water or food products leads to several diseases and even death. Recently, studies have been carried out to explore the biochemical and molecular mechanisms which contribute to As toxicity, accumulation, detoxification and tolerance acquisition in plants. This information has led to the development of the biotechnological tools for developing plants with modulated As tolerance and detoxification to safeguard cellular and genetic integrity as well as to minimize food chain contamination. This review aims to provide current updates about the biochemical and molecular networks involved in As uptake by plants and the recent developments in the area of functional genomics in terms of developing As tolerant and low As accumulating plants. Highlights: Arsenic affects plant growth and human health due to food chain contamination. Omics can be an important tool to identify arsenic associated molecular networks. Biotechnological interventions can modulate arsenic response in plants. This review updates gene mining and approaches to develop altered arsenic response.